FGF10 Is Required for Circumvallate Papilla Morphogenesis by Maintaining Lgr5 Activity - Zhang, Sushan; Choi, Hyuk Su; Jung, Han-Sung; Lee, Jong-Min (Frontiers in Physiology, 2018)
Taste buds develop in different regions of the mammal oral cavity. Adult stem cells in various organs including the tongue papillae are marked by leucine-rich repeat-containing G protein-coupled receptor 5 (Lgr5) and its homolog, Lgr6. Recent studies have reported that adult taste stem/progenitor cells in circumvallate papilla (CVP) on the posterior tongue are Lgr5-positive. In this study, we confirm the Lgr5 expression pattern during CVP development. A previous study reported that mesenchymal Fgf10 is necessary for maintaining epithelial Lgr5-positive stem/progenitor cells. To confirm the interaction between Lgr5-positive CVP epithelium and mesenchymal factor FGF10, reverse recombination (180-degree) was performed after tongue epithelium detachment. FGF10 protein-soaked bead implantation was performed after reverse recombination to rescue CVP development. Moreover, we reduced mesenchymal Fgf10 by BIO and SU5402 treatment which disrupted CVP morphogenesis. This study suggests that the crosstalk between epithelial Lgr5 and mesenchymal Fgf10 plays a pivotal role in CVP epithelium invagination during mouse tongue CVP development by maintaining Lgr5-positive stem/progenitor cells.